2017
DOI: 10.35196/rfm.2017.4.405-413
|View full text |Cite
|
Sign up to set email alerts
|

Type of Light and Formation of Basidiomata of Two Species of Edible Ectomycorrhizal Mushrooms Associated With Neo-Tropical Pines and the Description of Basidiomata Development

Abstract: Ectomycorrhiza is a mutualistic symbiosis of paramount importance in the functioning of forest ecosystems. Therefore, inoculation with ectomycorrhizal fungi, particularly edible species, has gained enormous relevance in the production of forest trees with economic importance. However, due to technical difficulties for the cultivation of ectomycorrhizal basidiomata associated with their host trees, factors influencing basidiomata formation have not been fully understood. This study evaluated the effect of two l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…& Broome spp. ( Rentería-Chávez, Pérez-Moreno, Cetina-Alcalá, Ferrera-Cerrato, & Xoconostle-Cázares, 2017 ; Villegas-Olivera et al, 2017 ) and Helvella cf. lacunosa Afzel.…”
Section: Controlled Mycorrhizal Synthesisunclassified
See 1 more Smart Citation
“…& Broome spp. ( Rentería-Chávez, Pérez-Moreno, Cetina-Alcalá, Ferrera-Cerrato, & Xoconostle-Cázares, 2017 ; Villegas-Olivera et al, 2017 ) and Helvella cf. lacunosa Afzel.…”
Section: Controlled Mycorrhizal Synthesisunclassified
“…Prior research has shown that well-mycorrhized seedlings can start producing fruiting bodies of their associated fungi under laboratory (growth chamber) or nursery conditions ( Godbout & Fortin, 1990 ; Danell & Camacho, 1997 ; Villegas-Oliveira et al, 2017 ; Ogawa et al, 2019b ), in some cases as early as 1 y or less after inoculation ( Guerin-Laguette et al, 2000a ; Yamada et al, 2001a ). This includes the prestigious Périgord black truffle successfully cultivated by Albert Verlhac 2 to 3 y after planting mycorrhizal Quercus pubescens Willd.…”
Section: Onset Of Fruitingmentioning
confidence: 99%
“…However, despite their importance, the factors that originate the sporome formation of edible ectomycorrhizal fungi have been scarcely studied. Previously, it has been reported that the light quality is a factor that influences the formation of ectomycorrhizal sporomes (Villegas-Olivera et al, 2017). In addition, it has also been shown that the application of electrical impulses stimulates the formation of sporomes both in saprotrophic and ectomycorrhizal fungi, including: Pholiota nameko, Lentinula edodes, Lactarius deliciosus, Laccaria laccata and Tricholoma matsutake (Guerin Laguette et al, 2000;Ohga et al, 2011;Takaki et al, 2009;Ohga et al, 2012).…”
mentioning
confidence: 99%